LINGUISTIC AND CULTURAL ASPECTS OF FAMILY JOKES IN ENGLISH AND UZBEK - Olimjonovna, Mirabdullayeva Zulfiyaxon (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study aims to conduct a cross-cultural comparative analysis of family-related humor in English and Uzbek cultures to uncover culturally embedded themes, social norms, and relational dynamics represented through jokes. Method: A qualitative content analysis was conducted on a dataset of 200 family-related jokes (100 English, 100 Uzbek), with particular attention to themes of marital dynamics, gender roles, and in-law relationships. Results: The analysis revealed distinct cultural orientations in humor: English family jokes predominantly reflect nuclear family structures and emphasize individualism, often using irony and understatement, while Uzbek jokes center on extended family hierarchies, traditional gender expectations, and the importance of collective family honor. Novelty: This study provides a novel contribution by situating family humor within a cross-linguistic and cross-cultural framework, highlighting how humor serves not only as entertainment but also as a vehicle for reinforcing or challenging cultural norms. The findings enrich the understanding of socio-cultural discourse in humor, offering implications for cross-cultural communication, translation studies, and sociolinguistics.